2000
DOI: 10.1590/s1516-35982000000300023
|View full text |Cite
|
Sign up to set email alerts
|

Níveis dietéticos de lisina para suínos da raça Landrace dos 15 aos 30 kg

Abstract: RESUMO -Com o objetivo de determinar a exigência nutricional de lisina total para suínos da raça Landrace, machos inteiros e fêmeas, de 15 a 30 kg de peso, foram conduzidos dois experimentos. Utilizaram-se 50 fêmeas no experimento I e 50 machos inteiros no experimento II, em delineamento em blocos casualizados, com cinco tratamentos, cinco repetições e dois animais por unidade experimental, em cada experimento. Os tratamentos consistiram de uma ração basal suplementada com cinco níveis de L-lisina.HCl, resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Similarly these results, Moretto et al (2000) observed that the lysine levels changing of 0.85 at 1.05% influenced in quadratic form the protein deposition tax in piglets that increase until 1.04% of this amino acid in 18% CP diet. Agreement these authors, there was best amino acid balance with the addition of lysine.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly these results, Moretto et al (2000) observed that the lysine levels changing of 0.85 at 1.05% influenced in quadratic form the protein deposition tax in piglets that increase until 1.04% of this amino acid in 18% CP diet. Agreement these authors, there was best amino acid balance with the addition of lysine.…”
Section: Resultssupporting
confidence: 77%
“…Moreover, the higher carcass protein percentage was 18.5%, greater that one obtained by Trindade Neto et al (2004), 16.5% with 1.25% of true digestible lysine in 19% CP diet. Moretto et al (2000) verified increasing linear effect in piglets feed with total lysine changing of 0.85 at 1.25% in 18% CP diets. Moreover, the authors recommended 1.15% of this amino acid in the diet.…”
Section: Resultsmentioning
confidence: 58%
“…This observation is confirmed in this study and is similar to the results of Oliveira et al (2006b), Zangeronimo et al (2006) and Abreu et al (2007). Such effects, however, were not observed by Moretto et al (2000) and Gasparotto et al (2001).…”
Section: Results and Discusssionmentioning
confidence: 68%
“…Gasparotto et al (2001), studying lysine levels that varied from 0.90 to 1.20 % of digestible lysine, with animals selected for fast growth, found a quadratic effect of lysine levels on intake in periods from 0 to 14 and 0 to 28 days of evaluation, but not in the total experimental period. Abreu et al (2007) also found no effect of lysine on feed intake, like Moretto et al (2000), Urynek & Buraczewska (2003), Toledo et al (2005), Oliveira et al (2006a) and Zangeronimo et al (2006). According to these studies, maintaining the amino acid profile of the diet does not influence the feed intake of animals.…”
Section: Results and Discusssionmentioning
confidence: 95%
“…O melhor resultado foi obtido com 1,09% desse aminoácido (Figura 2), semelhante ao encontrado por Moretto et al (2000), porém, inferior ao descrito por Trindade Neto et al (2000), que obtiveram os melhores resultados nos níveis de 1,08 e 1,16% de lisina digestível verdadeira, respectivamente, em suínos na fase inicial. Tabela 2 -Médias de ganho de peso diário, consumo diário de ração e conversão alimentar de leitões de 9 aos 21 kg alimentados com rações com diferentes níveis de proteína bruta e lisina digestível …”
Section: Resultsunclassified